LITERARY FEMINIST ECOLOGIES OF AMERICAN AND CARIBBEAN EXPANSIONISM - Battista, Christine M., 1981- author. ([S.l.])
1 online resource
Keywords: This book synthesizes ecofeminist theory, American studies, and postcolonial theory to interrogate what New Americanist William V. Spanos articulates as the "errand into the wilderness": the ethic of Puritanical expansionism at the heart of the U.S. empire that moved westward under Manifest Destiny to colonize Native Americans, non-whites, women, and the land. The project explores how the legacy of the errand has been articulated by women writers, from the slave narrative to contemporary fiction. Uniting texts across geographical and temporal boundaries, the book constructs a theoretical approach for reading and understanding how women authors craft counter-narratives at the intersection of metaphorical and literal landscapes of colonization. It focuses on literature from the United States and the Caribbean, including the slave narratives by Sojourner Truth, Harriet E. Wilson, and Harriet Jacobs, and contemporary work by Toni Morrison, Maryse Cond, Edwidge Danticat, and Native American writer Linda Hogan. It charts the contrast between America's earliest idyllic visions and the subsequent reality: an era of unprecedented violence against women of color and the environment. This study of many canonical writers presents an important and illuminating analysis of American mythologies that continue to impact the cultural landscape today. It will be a significant discussion text for students, scholars, and researchers in environmental humanities, ecofeminism, and postcolonial studies.